Assessing Migration Risk for Scientific Data Formats - Chris Frisz; Geoffrey Brown; Samuel Waggoner (International Journal of Digital Curation, 2012)
The majority of information about science, culture, society, economy and the environment is born digital, yet the underlying technology is subject to rapid obsolescence. One solution to this obsolescence, format migration, is widely practiced and supported by many software packages, yet migration has well known risks. For example, newer formats – even where similar in function – do not generally support all of the features of their predecessors, and, where similar features exist, there may be significant differences of interpretation.